Adipocytokines and hepatic fibrosis. (March 2015) - Saxena, Neeraj K.; Anania, Frank A.
Highlights Hepatic fibrosis, although reversible, can lead to cirrhosis if unchecked. Clinical therapy to prevent liver fibrosis progression is not available. Cirrhosis poses a significant increased risk for development of hepatocellular carcinoma. Measurements of key cytokines could be useful biomarkers of predicting NAFLD patients likely to have disease progression.